Determining the impact of a piggery on the Inhlavini and uMkhomazi Rivers, KwaZulu-Natal - Madibe, Reginah Jabulile (North-West University (South Africa), 2021)
This study was undertaken on the Inhlavini and uMkhomazi rivers, situated in the KwaZulu-Natal (KZN) province, South Africa (RSA). Its focus was on assessing the possible impact of a piggery (referred to as Piggery X, to keep its anonymity) on the condition of the rivers. Piggery X was directly discharging untreated effluent into the Inhlavini River, approximately 5 km upstream of its confluence with the uMkhomazi River. The activity was subsequently stopped by the National Department of Water and Sanitation (DWS); however, no rehabilitation was undertaken, to mitigate for any possible contamination that might have occurred. Since there was no rehabilitation undertaken, the study aimed at assessing if natural recovery had taken place, and if so, how effective it has been. A total of five monitoring points (three on the Inhlavini and two on the uMkhomazi rivers) were selected. The three sites on the Inhlavini River were: 1) Inhlavini Upstream of Impact Monitoring Point (referred to as IU); 2) Inhlavini Impact Monitoring Point (II); 3) Inhlavini Downstream of Impact Monitoring Point (ID). The two on the uMkhomazi River were: 1) uMkhomazi Upstream Monitoring Point (upstream of confluence) (UU); and uMkhomazi Downstream Monitoring Point (below confluence) (UD). Water quality variables (temperature, pH, electrical conductivity, total dissolved solids, potassium, copper, orthophosphate, suspended solids, chemical oxygen demand, nitrates and nitrites, E. coli and faecal coliforms) were mostly compliant to South African Water Quality Guidelines for Domestic Use and Agricultural Uses (Livestock and Irrigation); however, few variables (pH, copper and faecal coliforms) were slightly non-compliant to South African Water Quality Guidelines for Aquatic Ecosystem (DWAF, 1996). Macro-invertebrates were sampled at uMkhomazi River (UU and UD sites). Macro-invertebrates were not sampled at Inhlavini River as it was flooding in February 2020, and was dry in July and October 2020. Macro-invertebrates using SASS5 placed the uMkhomazi River within the ecological category A/B (EC A/B) at UU for both wet and dry season; whilst UD fell in EC A and EC B during wet and dry seasons, respectively, which indicates that the mentioned river was largely natural with few modifications. Overall, site IU showed slight contamination, possibly due to anthropogenic influence from the nearby village, and Ixopo area. At site II, there was a slight increase in analysed variables, but still within limits. However, there was a decrease/improvement in all analysed variables at site ID - possibly due to the natural recovery process, because of extensive good condition riverine-associated wetlands within that reach. It can thus be concluded that the system was not significantly impacted or was able to recover naturally; and therefore, there would not be a need for any manual rehabilitation of the system.
M (Environmental Management), North-West University, Potchefstroom Campus
Keywords: Bio-monitoring; Water quality; SASS5; Piggery; Pollution; Macro-invertebrates